Remediation of chlorpyrifos-contaminated soils by crude secondary metabolites of Trichoderma harzianum T213 and its effect on maize growth - LOEKAS SOESANTO; RISMA ARSI SUSANTI; ENDANG MUGIASTUTI; ABDUL MANAN; MURTI WISNU RAGIL SASTYAWAN; JOKO MARYANTO (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Soesanto L, Susanti RA, Mugiastuti E, Manan A, Sastyawan MWR, Maryanto J. 2022. Remediation of chlorpyrifos-contaminated soils by crude secondary metabolites of Trichoderma harzianum T213 and its effect on maize growth. Biodiversitas 23: 2464-2470. The study was conducted to determine the role of Trichoderma harzianum T213 crude secondary metabolites on the growth of maize plants and the reduction of chlorpyrifos on contaminated soils. A randomized block design was used in this study with four treatments. The treatments applied on chlorpyrifos contaminated soil were: without the application of secondary metabolites (0%) and the application of T. harzianum T213 crude secondary metabolites at the concentration of 50, 100, and 150%. Variables observed were residual levels of insecticide in maize, plant height difference, number of leaves, plant fresh weight, and root length. The results showed that the application of T. harzianum T213 crude secondary metabolites effectively increased plant growth, including plant height, the number of leaves, plant fresh weight, and root length compared to control on chlorpyrifos-contaminated soil. The highest percentage (99.54%) of the reduction of chlorpyrifos residue was the application of 100% T. harzianum T213 crude secondary metabolites. It was followed by applying 50 and 150% T. harzianum T213 crude secondary metabolites by 99.39 and 99.14%, respectively.